Evaluation of the prognostic value of the neutrophil to lymphocyte ratio, lactate dehydrogenase enzyme, and proteinuria in patients with acute pancreatitis admitted at Assiut University Hospitals and its correlation with Ranson's criteria scoring system - Lobna Abdel-wahid Ahmed; Abd-Alla Ismail Ali Kelani; Fady Refaat Edwar Nasr-Allah (SpringerOpen, 2020)
Abstract Background Acute pancreatitis is a relatively common acute medical presentation that may progress beyond the pancreas to cause multi-organ failure or death. It is associated with high morbidity and mortality with mortality rates changing little in the past few decades despite advances in intensive care and surgical management. Early evaluation of acute pancreatitis severity is essential to allow the clinician to predict the patient's clinical course, estimate the prognosis, determine the need for intensive care unit admission, and prevent complications. So, the purpose of our study is to evaluate the prognostic value of the neutrophil to lymphocyte ratio, lactate dehydrogenase enzyme, and proteinuria in patients with acute pancreatitis and its correlation with Ranson's criteria scoring system as new, rapid, and easy parameters to predict severity of acute pancreatitis. Results The mean age of patients in years was 47.97, and the median was 52 with a range of ages between 18 and 87; 38% of the patients included were males, and 61% were females. The mean Ranson's score was 2.77 ± 1.4, and the median was 3 with a range of 0-6; 44.5% of patients included have low severity, 42.4% have mild severity, and 13.1% of patients have high severity. Neutrophil to lymphocyte ratio both at the time of admission and after 48 h of admission was significantly increasing with an increase in disease severity with a P value of < 0.001 that was statistically significant. Lactate dehydrogenase enzyme at the time of admission was also significantly increasing with diseased severity with a P value of 0.001 that was statistically significant and the same for lactate dehydrogenase enzyme level after 48 h of admission with a P value of 0.002 that was also statistically significant. Proteinuria is positive only in 15.2% of patients and with the same result after 48 h of admission. Conclusion The neutrophil to lymphocyte ratio gives a rapid impression of the extent of the inflammatory process, and it can effectively predict severity at the time of admission and even after 48 h of admission and can also differentiate between patients with mild and severe acute pancreatitis in both calcular and non-calcular cause-dependent acute pancreatitis patients. Lactate dehydrogenase can be used to predict severity in calcular cause-dependent acute pancreatitis patients only at the time of admission and after 48 h of admission. Proteinuria in urine analysis on admission and after 48 h does not seem to be a reliable predictor for disease severity in acute pancreatitis.